Nurses’ experiences on the use of Afrikaans for nursing documentation and handovers at a central hospital in the Western Cape - Mgoqi, Mangoyi (Stellenbosch : Stellenbosch University, 2017)
Thesis (MCur)--Stellenbosch University, 2017.